1986
DOI: 10.1007/bf02553027
|View full text |Cite
|
Sign up to set email alerts
|

Bowel symptoms in an apparently well population

Abstract: The aim of this study was to determine the prevalence of various kinds of bowel behavior and symptoms thought to be indicative of colorectal cancer in people randomly selected from the community. A probability sample of 330 dwellings in the inner western suburbs of Sydney yielded 202 completed interviews with occupants aged 30 years and older. Eight percent reported annoying abdominal pain that had lasted for two weeks or more in the preceding six months, while 19 percent reported a feeling of incomplete evacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 13 publications
2
33
1
Order By: Relevance
“…For instance, the use of herbal preparations like teas which also contain anthranoid ingredients, was probably not noticed. This explains why laxative use was reported in only 11.9% of the patients in our study, in contrast to prospective studies where this percentage ranged between 17 and 22% [2][3][4],…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…For instance, the use of herbal preparations like teas which also contain anthranoid ingredients, was probably not noticed. This explains why laxative use was reported in only 11.9% of the patients in our study, in contrast to prospective studies where this percentage ranged between 17 and 22% [2][3][4],…”
Section: Discussioncontrasting
confidence: 54%
“…About 20% of the population is consuming laxatives regularly [2][3][4], Mutagenic effects of certain anthranoids could be shown in vitro [5][6][7][8] but the clinical relevance of these experimental re sults is not clear up to now. Epidemiologic studies gave no evidence for any association between laxative use and development of colorectal cancer in humans [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The problem may be even more common in younger adults because of under-reporting to physicians [1] . For example, a community-based study of 1643 adults ages 20 to 64 found that 13 percent reported blood on wiping.…”
Section: Introductionmentioning
confidence: 99%
“…According to health surveys conducted in the United States, 15-20% of the US population com plain of constipation [7,8], Secondary to its frequent occurrence, even a minor increase in risk associated with constipation could have an appreciable influence on the overall inci dence of colorectal cancer. Cathartics are widely used for treatment of constipation, and from published case-control studies it appears that again 15-20% of all adults use some type of laxative on a regular basis to soften their bowel movement and increase its frequency [9,10]. It might be hypothesized that the cathartics so commonly used to treat consti pation rather than the constipation itself might be the main responsible factor for the increased incidence of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%